Growth and gonadal development in diploid and triploid turbot (Scophthalmus maximus) - Cal, Rosa; Vidal, Sergio; Gómez, Castora; Álvarez-Blázquez, Blanca; Martínez, Paulino; Piferrer, Francesc (Aquaculture, 2006)
10 pages, 5 figures, 1 table This study determined the effect of triploidy on the survival, growth and gonadal development of turbot from 6 to 48 months of age. From 6 to 24 months of age (first sexual maturity), survival was similar in both ploidies (P > 0.05). From 24 to 48 months of age, after the first sexual maturity, survival was 91.9% in diploids and 100% in triploids, which did not exhibit the post-spawning-associated mortality. Growth was similar for both ploidies during the first year of life. After that, triploids grew significantly (P < 0.05) more that diploids, with more marked differences after each spawning season. From 24 to 48 months, the average weight difference between both ploidies was 11.4 ± 1.9%, ranging from 4.3 to 23.0%. At 47 months of age, the biomass of triploids was 10.3% greater in total weight and 14.3% greater in eviscerated weight. Gonads of triploid males were similar to that of diploids, whereas in triploid females, they were significantly smaller and rudimentary. A histological analysis carried out at 47 months of age showed complete sterility of triploids in both sexes. Sex ratio was 1 male (M):0.6 female (F), for diploids, significantly (P < 0.05) different from 1:1, and 1 M:3.3 F for triploids, significantly (P < 0.05) different from 1:1 and from the diploids. Since females grow more than males, culture of triploids benefited from the high female ratio, which helped to reduce size dispersion. In addition, their sterility allowed better performance by avoiding the reduction in growth that takes place during the spawning periods. Together, these observations indicate that triploidy induction can be an interesting option for turbot aquaculture, especially for the production of large-size fish of more than 2 years of age Peer reviewed